Aggregation induced emission enhancement and chromism properties of a vinyl bridged naphthalene diimide dimer. (July 2022) - Long, Haijun; Guo, De; Wang, Liyuan; Liu, Zitong; Li, Shayu; Liang, Xianfeng; Chen, Yanlin; Yang, Zhiwei; Li, Jing; Dong, Lichun; Tan, Luxi
Abstract: A vinyl bridged 1, 4, 5, 8-Naphthalenetetracarboxylic diimide (NDI) dimer, DNV was synthesized, which exhibits relatively strong Aggregation Induced Emission Enhancement (AIEE) behaviour with absolute quantum yield of 13.6%, as well as wide Aggregation Induced Chromism (AIC) phenomenon (over 100 nm), from green to orange emission. The density functional theory (DFT) and coupled cluster calculations reveal a unique twisted packing mode of DNV in its aggregated state, and mild intermolecular CT between the stacked DNV molecules was also observed. This J -aggregation like molecular arrangement and the net CT might contribute to the long wavelength emission. The bio-imaging capability of DNV is also examined by a living cell experiment. Graphical abstract: Image 1 Highlights: A vinyl bridged 1, 4, 5, 8-Naphthalenetetracarboxylic diimide (NDI) dimer, DNV was synthesized and fully characterized. Aggregation induced strong emission enhancement (AIEE) and large fluorescence chromism (AIC) were realized. The theoretical calculations revealed a unique twisted packing mode for DNV in its aggregated state (dimer state). Bio-imaging capability of the DNV material was also examined by living cell experiment.